Governance of Municipal Social Services: Making Citizens Aspirations Known - Pastor Seller, Enrique (Cuadernos de Trabajo Social, 2012)
The article presents an analysis of the mechanisms, practices and processes for participation in municipal social services and the dimensions of analysis and professional intervention with which they intensify their influence on the system. It is structured in three parts: the first refers to a brief theoretical and normative framework, emphasizing the analysis that the new Autonomous Social Services Laws make of the participation of citizens and users at the local level. The second section presents a characterization of types of mechanisms and processes of participation in municipal social services and finally, proposals and alternatives to improve the system and the processes and practices designed to enhance participation in the construction of social policies at the local level are systematized.
Keywords: Social services; Local government; Participation; Municipal social policies.